Dumbo [videorecording (DVD)] - Sharpsteen, Ben; Holloway, Sterling; Brophy, Edward, 1895-1960; Baskett, James, 1904-1948; Bing, Herman, 1889-1947; Bletcher, Billy, 1894-1979; Wallace, Oliver, 1887-1963; Churchill, Frank, 1901-1942; Aberson, Helen (Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2011)
The stork delivers a baby elephant to Mrs. Jumbo, who happens to be a veteran of the circus, but the newborn is soon ridiculed because of his truly gigantic ears and is dubbed "Dumbo". Dumbo is relegated to the circus' clown acts. It is up to Dumbo's only true friend, Timothy Q. Mouse, to assist Dumbo to achieve his full potential.